PROSPECT OF MINERAL DEPOSITS IN THE CENTRAL FLORES ISLAND, EASTERN INDONESIA - Harahap, Bhakti H; Abidin, Hamdan Z; Utoyo, Harry; Djumhana, Duddy; Yuniarni, Rum (Pusat Survei Geologi, 2015)
Field data on the Central Flores Island, Eastern Indonesia (Sikka and Ende Regencies) together with chemical analyses allow us to discuss the prospect of mineral occurrences in this inner arc volcanic zone. Geologically, the area is dominated by Tertiary-Quaternary volcanic and sedimentary rocks, sitting unconformably on the siliceous sedimentary basement of Pre-Tertiary ages. The Tertiary volcanic rocks referred to as Kiro Formation consist of tuff, andesite lava, breccia and green tuff, while the sedimentary rocks are dominated by sandstone and claystone. The Pre-Tertiary basement rocks and the Kiro Formation were intruded by Late Miocene granite, granodiorite, diorite and andesite resulted in hydrothermal alteration and mineralization. The identified hydrothermal alteration includes chlorite, zeolite, kaolinite, jasper and silica. Ores deposits are represented by iron ore, manganese, gold, base metal and iron sands. Style of mineralization is disseminated features, cavity filling, replacement and veins. In general, quartz veins show vuggy, comb and bossa / bladed pseudomorph calcite texture. Sample analyses from quartz veins show that gold (Au) value ranges from 3 - 39 ppm, copper (Cu) : 15-133 ppm, lead (Pb) : 9 - 123 ppm, Zinc (Zn) : 7 - 31 ppm. Within silicified rocks, gold value ranges from <2 - 5 ppm, Cu : 6-546ppm, Pb : 28 - 1181 ppm, Zn : 18-3906 ppm. In contrast within altered rocks, Au : <2-55ppb, Cu : 9-199 ppm, Pb : 24 - 54 ppm, Zn: 40 - 142 ppm. The content of iron within ore veins range from 45.55 - 60.41%; manganese ranges from 231-8330 ppm (altered rock) and iron sands range from 4.22 - 50.83% magnetite. The result of the preliminary works in the area has been revealed that the Sikka and Ende Regencies could be traced for several mineral deposits occurrences such as epithermal, porphyry, skarn and volcanogenic massive sulfide of Kuroko type. Keyword : sikka, green tuff, skarn, volcanogenic, porphyry, epithermal